The Effect Of Return On Assets, Return On Equity, Net Profit Margin, Earning Per Share, And Operating Profit Margin On Stock Prices Of Banking Companies In Indonesia Stock Exchange - Choiriyah, Choiriyah; Fatimah, Fatimah; Agustina, Sri; Ulfa, Ulfa (International Journal of Finance Research, 2020)
This study aims to determine the effect of return on assets (ROA), return on equity (ROE), net profit margin (NPM), earning per share (EPS) and operating profit margin (OPM) on the stock prices of banking companies on the Indonesia Stock Exchange. This type of research is associative research. Secondary data in this study is in the form of banking financial statements. The total population used in this study were 32 banking companies, and the samples that met the research criteria were eight banking companies listed on BEI. The analytical model used in this study is multiple linear regression analysis. The analysis results show that ROA, ROE, NPM, EPS, and OPM together have a significant effect on the stock prices of banking companies on the Indonesia Stock Exchange (IDX). On the other hand, coefisiens of ROA, NPM and OPM have no significant effect on the Stock Price of banking companies on the Indonesia Stock Exchange (IDX). In contrast, ROE and EPS significantly affect the Stock Price of banking companies on the Indonesia Stock Exchange (IDX).